Clinical Evidence and Risk Factors for Reproductive Disorders Caused by Bacterial Infections in Meat Goats in Northeastern Thailand - Sarinya Rerkyusuke; Sawarin Lerk-u-suke; Anucha Sirimalaisuwan (Veterinary Medicine International)
The objective of this study was to identify risk factors related to reproductive disorders caused by bacterial infections in goats in northeastern Thailand. Two hundred twenty farms were investigated, and 49 herds were found to have clinical reproductive disorders. Moreover, 96% (47/49) of herds showing clinical reproductive failure preferred to circulate bucks between herds. A total of 118 sera, including 85 clinical reproductive disorder cases such as abortion (n = 70), abortion with arthritis (n = 1), orchitis (n = 3), repeat breeder (n = 6), sterile (n = 1), and weak kids (n = 4), and 33 bucks’ circulations were serologically tested for bacterial infections caused by Coxiella burnetii, Chlamydophila abortus, and Brucella spp. Results showed 69% (81/118 cases) were seropositive for Q fever (n = 55; 46.61%), brucellosis (n = 8; 6.78), and chlamydiosis (n = 18; 15.25%), respectively; 82% of herds (40/49 herds) were infected with at least one of those diseases. Moreover, 40% of infected herds (16/40) had coinfection among the three of those diseases. Approximately 60% (20/33) of buck circulation showed seropositivity to at least one of the diseases, and 85% of infected bucks were seropositive for Q fever (17/20). Buck circulation between herds is a risk factor for diseases on farms (p=0.001); odds ratio (OR = 109.29; 95% confidence interval (CI) = 6.61–1,807.38). Moreover, the annual brucellosis test is a protective factor against reproductive failure cases on farms (p=0.022; OR = 0.45; 95% CI = 0.23–0.89). Reproductive disorder cases can be caused by sexual transmission, so buck circulation can yield Q fever, brucellosis, and chlamydiosis in communities. This investigation is the first report of chlamydiosis infection in our area. Concerning Q fever, chlamydiosis, and brucellosis are zoonotic diseases that impact animal health and production losses. Control and prevention measures related to risk factors together with active surveillance programs should be incorporated into client education.